2020
DOI: 10.2196/21632
|View full text |Cite
|
Sign up to set email alerts
|

Physical Distancing Measures and Walking Activity in Middle-aged and Older Residents in Changsha, China, During the COVID-19 Epidemic Period: Longitudinal Observational Study

Abstract: Background Physical distancing measures taken to contain COVID-19 transmission may substantially reduce physical activity levels and cause individuals to adopt a more sedentary lifestyle. Objective The objective of this study is to determine if there was any change in daily steps, an important component of daily physical activity, and examine risk factors for frequent low daily steps during the COVID-19 epidemic. Method… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
78
4

Year Published

2021
2021
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(85 citation statements)
references
References 35 publications
(45 reference statements)
3
78
4
Order By: Relevance
“…They also reported less time engaged in leisure-related vigorous physical activity and total physical activity during the COVID-19 outbreak. Several cross-sectional and longitudinal studies conducted among other population groups echoed similar patterns in how the COVID-19 pandemic unfavorably affected people's active movement behaviors [25][26][27][28][29][30]. For example, a national study conducted in Canada found that children and youth reported higher sedentary behaviors and lower physical activity during the COVID-19 outbreak; the study found that less than 5% of children and less than 1% of youth met the combined 24-hour movement behavior goals for physical activity, sedentary behavior, and sleep [25].…”
Section: Principal Findingsmentioning
confidence: 77%
“…They also reported less time engaged in leisure-related vigorous physical activity and total physical activity during the COVID-19 outbreak. Several cross-sectional and longitudinal studies conducted among other population groups echoed similar patterns in how the COVID-19 pandemic unfavorably affected people's active movement behaviors [25][26][27][28][29][30]. For example, a national study conducted in Canada found that children and youth reported higher sedentary behaviors and lower physical activity during the COVID-19 outbreak; the study found that less than 5% of children and less than 1% of youth met the combined 24-hour movement behavior goals for physical activity, sedentary behavior, and sleep [25].…”
Section: Principal Findingsmentioning
confidence: 77%
“…This study is the first to examine the heterogeneity in longitudinal changes in physical activity during the COVID-19 pandemic. Building on recent longitudinal studies, which reported a general decline in physical activity at the start of the pandemic, [10][11][12][13][14][15]25 our analyses identified six unique classes of growth trajectories of physical activity. Three of these classes were stable, showing little change over time, including the inactive (11.6%), the fairly active (22.2%) and the highly active (28.6%).…”
Section: Discussionmentioning
confidence: 99%
“…Being female, younger, single, a parent, and from an ethnic minority group as well as having poor health, lower education and income, and no access to outside space have been associated with lower physical activity during lockdown. 11,12,15,20,21 However, findings have been inconsistent, and many studies have only examined physical activity at one point early in the pandemic. It therefore remains unclear whether similar factors are associated with trajectories of physical activity throughout lockdown and the easing of restrictions.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, community-dwelling older people living in urban areas stayed at home and became socially isolated as a result of both pandemic response measures as well as anxiety-induced self-imposed isolation. As a result of the mandatory self-isolation, physical activity appears to decline, affecting subjective well-being [ 8 , 9 ]. A large body of evidence supports the benefit of regular physical activities in reducing health risks [ 10 ].…”
Section: Introductionmentioning
confidence: 99%